Interventions Aiming to Promote Active Commuting in Children and Adolescents: An Evaluation From a Sex/Gender Perspective - Marzi, Isabel; Emmerling, Sandra; Demetriou, Yolanda; Bucksch, Jens; Schulze, Carolin; Brindley, Catherina; Reimers, Anne Kerstin (Frontiers in Sports and Active Living, 2020)
Active commuting (AC) provides numerous health benefits and is one way to improve physical activity in children and adolescents. Boys are more likely to use active transport modes than girls. Girls and boys benefit differently from interventions that promote AC. The aim of this systematic review is to evaluate the effects of interventions on girls and boys and to appraise the extent to which previous studies have taken sex/gender into account. Eleven electronic databases were searched to identify all relevant randomized and non-randomized controlled trials based on a priori defined eligibility criteria. Two independent reviewers screened the literature for eligibility and assessed risk of bias. Semiquantitative analyses were conducted to evaluate the effects of intervention effects by taking sex/gender aspects into account. To evaluate sex/gender considerations in interventional studies, a recently developed sex/gender checklist was applied. Twelve studies were included that examined intervention effects on AC in girls and boys. Three intervention studies showed significant effects in increasing AC, with one study favoring girls, one favoring boys, and another focusing on a single sex/gender (only girls). According to the checklist, the overall sex/gender rating highlighted a lack of information in sex/gender consideration. Studies with and without significant effects indicated no differences in the sex/gender checklist. The results indicate that sex/gender is not considered adequately in primary interventional research on AC. To evaluate the effectiveness of intervention in boys and girls, detailed analyses of sex/gender are required, and better reporting about sex/gender-specific intervention content is necessary. In future health research to promote AC, sex/gender should be systematically taken into account.